Intussusception related to Ogilvie's syndrome caused by herpes zoster infection - Supangat; Yuli Lusiana Sari; Fuad Adi Prasetyo; Nastiti Widoretno; Madha Qoyyulledy Tursina (Elsevier, 2022)
Background: A case of intestinal pseudo-obstruction (Ogilvie's syndrome) caused by herpes zoster infection, likewise appendicitis in infants and newborns is very rare. An understanding of the rare association is important to provide proper management and prevent associated morbidity and mortality. Case presentation: A 5-year-old female child was brought to dr. Soebandi General Hospital by her parents with constipation, vomiting, and enlarged stomach. In the physical examination there were distended abdomen, increased bowel sound, and tenderness throughout the abdomen, initially diagnosed as peritonitis due to perforated appendicitis. Plain abdominal x-ray shows intestinal gas enhancement and bowel dilatation and in the left lateral decubitus (LLD) position photo revealed multiple step ladder appearances. Then this patient was performed an exploratory laparotomy. There we found peritonitis with intussusception. This bowel obstruction was associated with red vesicles that indicate the herpes zoster virus infection. Conclusions: This patient was suffering intussusception related to Ogilvie's syndrome caused by herpes zoster infection. Intussusception can induce Intestinal pseudo-obstruction or total obstruction. Acute colonic pseudo-obstruction (Ogilvie's syndrome) is a disorder characterized by acute dilatation of the colon in the absence of an anatomic lesion that obstructs the flow of intestinal contents.